MORPHOLOGICAL , BIOCHEMICAL AND GROWTH CHARACTERISTICS OF SERRATIA STRAINS ISOLATED FROM SARDINE (SARD!NELLA LONGICEPS) - NAMBIAR, V NARAYANAN; SURENDRAN, P K; IYER, K MAHADEVA (Fishery Technology, 2017)
Two aerobic, gram-negative asporogenous, red-pigmented" rod-shaped bacterial strains were isolated from oil sardine ( Sardinella longiceps). Their morphological, biochemical and growth characteristics are reported. The pigment was identified to be a prodigiosene. The strains were found to resemble Serratia plynmthica. Effect of temperature and certain carbohydrates on pigmentation was also studied. Iron was found to inhibit pigmentation, and mannitol or sorbitol removed s.uch inhibition.